A study on the determinants of foreign direct investment in Malaysia perspective / Abdul Ubaidillah Ab Rahman - Ab Rahman, Abdul Ubaidillah (Bachelor Of Business Administration (Hons) Marketing, 2013)
The purpose of this study is to investigate the best determinants of foreign direct investment (FDI) flows into Malaysia. This paper investigates whether FDI determinants affect FDI based on annual data over the period 1973-2010 for Multiple Linear Regression Analysis. The regression analysis tests identify the relationship among the variables in the study. The results of the FDI equation indicate that FDI flows in Malaysia are positively influenced by market size and exchange rate while negatively by infrastructure. The limitations of the study are based on the data set which could be found are limited which is lack of data in the FDI flows into Malaysia. The main objective of this study is to identify the factors that influence FDI flows into Malaysia. The secondary objective of this study is to examine the relationship between FDI determinants with the FDI flows in Malaysia. Finding suggests government that FDI is a key role for economic development and channels for the dissemination of modern technology in the future